The Kumbis and Nagatis Formations and the Helmeringhausen Gabbro: Oldest undeformed rocks of the Sinclair Supergroup in Namibia. (May 2020) - Harris, M.; Cornell, D.H.; Mapani, B.S.; Malobela, T.; Lundell, C.; Jonsson, A.K.
Abstract: The Mesoproterozoic rocks of the Kumbis and Nagatis Formations and Helmeringhausen Gabbro in Southern Namibia are now recognised as the oldest rocks in the sedimentary and volcanic Sinclair Supergroup. The stratigraphic subdivision and plate tectonic setting are still debated and reliable ages are sparse. This work investigates the relatively undeformed felsic and mafic lava of the Kumbis Formation, rhyolitic lava of the Nagatis Formation and the intrusive Helmeringhausen Gabbro. Microscopic and field investigation reveals no evidence of regional metamorphism in these units. Ion probe U–Pb zircon dating yields ages of 1374 ± 7 Ma to 1358 ± 5 Ma (2σ) for the Kumbis Formation, 1363 ± 11 Ma for the Nagatis Formation and 1372 ± 12 Ma for the Helmeringhausen Gabbro. These dates are in contrast to the published stratigraphy in which the Helmeringhausen Gabbro was regarded as much older than the Kumbis Formation and both were excluded from the Sinclair Supergroup, whereas the Nagatis Formation was considered to be younger and was included as the oldest unit of the Sinclair Supergroup. Lu–Hf data on zircon indicates different magma sources for the Kumbis and Nagatis Formations, implying that although they are time equivalent, they are not co-magmatic. The geochemical data suggests that the most felsic rocks contain large amounts of older crustal material, from which their apparent subduction signatures were inherited. The more mafic rocks also contain minor crustal components mixed with material derived from depleted mantle. The Helmeringhausen Gabbro is similar to coeval hybrid gabbros at Neuhof Valley 150 Km to the north and they are grouped in the intrusive Helmering Suite. Taking the regional context into account, these oldest rocks of the Sinclair Supergroup probably formed in a rift environment which split the Rehoboth Province apart at the beginning of the Mesoproterozoic Namaqua-Natal Wilson Cycle. Highlights: Two distinct magmas, Palaeoproterozoic to Archaean crustal assimilation. Nagatis, Kumbis Formation and Helmeringhausen Gabbro are coeval. Originated at 1.37 Ga in Rehoboth Province, undeformed by 1.2 Ga Namaqua collision. Subduction geochemical signature could have been inherited from older crustal rocks.